2018
DOI: 10.18203/2349-2902.isj20181418
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of surgery for perforated peptic ulcer in modern times

Abstract: Background: A laparotomy for peritonitis due to perforated peptic ulcer is one of the commonest emergency operations done by a general surgeon and is still associated with a marked mortality and morbidity. The aim was to assess the current mortality and morbidity in patients operated for perforated peptic ulcer and to identify the factors associated with increased mortality in these patients.Methods: All adult patients operated for perforated peptic ulcer over a period of one year were included in this prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In current study, out of 203 patients 145 (71.4%) were male while 58 (28.6%) were female. There were 53 (96.36%) males and 02 (3.64%) females found in the study of Vats R, et al 15 . Lee FY, et al 16 In recent study, in distribution of site of perforation, 121 (59.6%) patients had duodenal perforations while 82 (40.4%) had gastric ulcer 19 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In current study, out of 203 patients 145 (71.4%) were male while 58 (28.6%) were female. There were 53 (96.36%) males and 02 (3.64%) females found in the study of Vats R, et al 15 . Lee FY, et al 16 In recent study, in distribution of site of perforation, 121 (59.6%) patients had duodenal perforations while 82 (40.4%) had gastric ulcer 19 .…”
Section: Discussionmentioning
confidence: 77%
“…Lee FY, et al 16 In recent study, in distribution of site of perforation, 121 (59.6%) patients had duodenal perforations while 82 (40.4%) had gastric ulcer 19 . The study of Vats R, et al 15 found the site of perforation as 29 (63.1%) had duodenal perforations while 17 (36.9%) had gastric. In the study of Lee FY, et al 16 , duodenal perforation accounted for 344 (78.9%) cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The choice of surgical technique, laparoscopy versus laparotomy, varies depending on the patient’s preoperative clinical status, surgeon expertise/preference, and location of defect, with the goal of short operative time. It has been widely reported that open abdominal surgery increases postoperative pain and is associated with higher morbidity (ventral incisional hernia rate, surgical site infection, postoperative respiratory compromise, delayed recovery times, and dehiscence) when compared to laparoscopic surgery [ 9 , 10 ]. Some studies have shown laparoscopy to lessen these postoperative variables and is associated with fewer complications (i.e., surgical site infection, length of stay (LOS), better cosmetic outcomes) than open repair [ 1 , 9 , 11 ].…”
mentioning
confidence: 99%
“…It has been widely reported that open abdominal surgery increases postoperative pain and is associated with higher morbidity (ventral incisional hernia rate, surgical site infection, postoperative respiratory compromise, delayed recovery times, and dehiscence) when compared to laparoscopic surgery [ 9 , 10 ]. Some studies have shown laparoscopy to lessen these postoperative variables and is associated with fewer complications (i.e., surgical site infection, length of stay (LOS), better cosmetic outcomes) than open repair [ 1 , 9 , 11 ]. Despite these favorable outcomes, laparoscopic repair is less commonly used, owning to longer operative times in less experienced centers, higher incidence of reoperations owning to leakage at the repair site, and higher incidence of intraabdominal fluid collections secondary to inadequate lavage and the requirement of extensive surgical skill [ 12 ].…”
mentioning
confidence: 99%